Identification of an exosomal miRNA signature in newly diagnosed essential hypertensive adults - Tan, Paulina Pei Suu (2025)
Background: Hypertension is a leading risk factor for cardiovascular disease (CVD) and premature death globally. Less than half of adults with hypertension are properly diagnosed and treated, highlighting a critical gap in current healthcare practices. The limitations of existing blood pressure measurement methods make it challenging to detect early cases of hypertension, which are often asymptomatic and, consequently, commonly undetected. This indicates the need for improved diagnostic and treatment strategies, particularly through precision medicine approaches. MicroRNAs (miRNAs) serve as master regulators of gene expression and are transported extracellularly by exosomes in various body fluids including plasma. Exosomal miRNAs have been implicated in hypertension development and have potential as non-invasive disease biomarkers. However, the profile of exosomal miRNA in a multi-ethnic population of essential hypertensives has yet to be elucidated.